Special issue on Mexican International Conference on Artificial Intelligence, MICAI 2014 and 2015 - Ponce, Hiram; González-Mendoza, Miguel; Martínez-Villaseñor, Ma. Lourdes (Soft computing (Berlin, Germany), 2017)
MICAI is an annual conference that disseminates and promotes growth of outstanding research works in all areas of artificial intelligence (AI), including but not limited to: expert systems and knowledge-based systems, knowledge representation and acquisition, multi-agent systems and distributed AI, natural language processing, intelligent interfaces, computer vision, machine learning, pattern recognition, soft computing, reasoning, robotics, planning and scheduling, among others. [...]the paper A 3-SPS-1S Parallel Robot-Based Laser Sensing for Applications in Precision Agriculture by Ricardo Zavala-Yoe, Ricardo A. Ramírez-Mendoza and Silverio García-Lara presents an intelligent control for a parallel robot for precision agriculture. A closed-loop control system is implemented, using a fuzzy logic controller and an artificial neural network-based model of the robot.